The influence of safety-specific transformational leadership on the safety behaviors: The mediating effect of safety climate and safety motivation and the moderating effect of trust in leader - Jung, HaJin; Lee , Suran; Sohn, YoungWoo (Korean Journal of Industrial and Organizational Psychology, 2015)
This study examined the influence of safety-specific leadership style (transformational, passive) on safety motivation and safety behaviors. Specifically, the study examined the sequential mediating effect of group-level safety climate and autonomous safety motivations (intrinsic, identified regulation) on the relationship between safety-specific transformational leadership (SSTL) and safety behaviors (participation, compliance) by using structural equation modeling. The study also investigated the moderating effect of trust in leader on the relationship of safety-specific leadership and group-level safety climate. Survey data were gathered from 440 military personnel in the Republic of Korea Navy. Results showed that SSTL predicted both safety participation and compliance through the sequential effect of group-level safety climate and intrinsic safety motivation. However, the path to the safety participation was not significant when identified regulation safety motivation was mediated. Safety-specific passive leadership (SSPL) also predicted safety behaviors through safety climate and motivation by the identical process of SSTL, but the effect was negative. Also, on the relationship between safety climate and safety motivation, group-level safety climate had more effect on intrinsic safety motivation than identified regulation safety motivation. On the relationship between safety motivation and safety behavior, intrinsic motivation had more effect on safety participation than compliance. Trust in leader had a moderating effect on the link between SSTL and group-level safety climate. However, the moderating effect was not significant on the association between SSPL and group-level safety climate. Based on these results, the implications and directions for future research were discussed.